PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN INTENSITAS MODAL TERHADAP TINGKAT PENGHINDARAN PAJAK PADA PERUSAHAAN - Nugraha , Erik; Hildayanti , Muti; Avianty, R. Rita; Laksana , Reksha (Universitas Sangga Buana, 2024)
The aim of this study was to examine the impact of Corporate Social Responsibility and Capital Intensity on Tax Avoidance using a Quantitative Approach. The sample consisted of 11 Food and Beverage Industry Sub-Sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period, resulting in 55 observations gathered through the Purposive Sampling Method. The data analyzed was Secondary Data. Panel Data Regression Analysis was conducted using EVIEWS 12. The findings indicated that the Corporate Social Responsibility variable had a positive and significant influence on Tax Avoidance, with a Probability value of 0.0055. Conversely, the results demonstrated that Capital Intensity did not have a significant impact on Tax Avoidance, with a Probability value of 0.0702. Simultaneously, both Corporate Social Responsibility and Capital Intensity have a significant and positive impact on Tax Avoidance. The Probability value is 0.000002.